2021
DOI: 10.1186/s12859-021-04182-9
|View full text |Cite
|
Sign up to set email alerts
|

Rapid protein sequence evolution via compensatory frameshift is widespread in RNA virus genomes

Abstract: Background RNA viruses possess remarkable evolutionary versatility driven by the high mutability of their genomes. Frameshifting nucleotide insertions or deletions (indels), which cause the premature termination of proteins, are frequently observed in the coding sequences of various viral genomes. When a secondary indel occurs near the primary indel site, the open reading frame can be restored to produce functional proteins, a phenomenon known as the compensatory frameshift. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 58 publications
1
18
0
Order By: Relevance
“…Few studies have been reported regarding FSMs in the evolution of viruses, including the viruses in the 13 families (Hughes, et al 2010; Taubenberger and Kash 2010; Breitbart, et al 2017; Simmonds, et al 2017; Zell, et al 2017; Chen, et al 2018; Laenen, et al 2019; Radoshitzky, et al 2019; Rima, et al 2019; Garrison, et al 2020; Hughes, et al 2020; Sun, et al 2022; Zmasek, et al 2022). This could be partially because researchers usually focused on virus evolution on small scales (e.g., intra-species evolution or microevolution of influenza virus or SARS-CoV-2), and FSMs are relatively rare in virus evolution on small scale, as revealed by this report and a previous report (Park and Hahn 2021). Consequently, we had the opportunity in this study to reveal frequencies and multiple features of FSMs in virus evolution on various scales for the first time.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Few studies have been reported regarding FSMs in the evolution of viruses, including the viruses in the 13 families (Hughes, et al 2010; Taubenberger and Kash 2010; Breitbart, et al 2017; Simmonds, et al 2017; Zell, et al 2017; Chen, et al 2018; Laenen, et al 2019; Radoshitzky, et al 2019; Rima, et al 2019; Garrison, et al 2020; Hughes, et al 2020; Sun, et al 2022; Zmasek, et al 2022). This could be partially because researchers usually focused on virus evolution on small scales (e.g., intra-species evolution or microevolution of influenza virus or SARS-CoV-2), and FSMs are relatively rare in virus evolution on small scale, as revealed by this report and a previous report (Park and Hahn 2021). Consequently, we had the opportunity in this study to reveal frequencies and multiple features of FSMs in virus evolution on various scales for the first time.…”
Section: Discussionmentioning
confidence: 73%
“…The copyright holder for this preprint this version posted July 21, 2022. ; https://doi.org/10.1101/2022.07.20.500745 doi: bioRxiv preprint Previous reports classified FSMs into 2-indel compensatory FSMs and non-compensatory FSMs, and one report suggested that their frequencies are similar (Park and Hahn 2021;Rogers, et al 2021). Here we identified that, from a broader view, there were 3-, 4-, and 5-indel compensatory FSMs in virus evolution, besides 1-indel non-compensatory FSMs and 2-indel compensatory FSMs (fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been described in various viral genomes that frameshifting due to nucleotide insertions or deletions (indels), which may cause the premature termination of protein synthesis, can be restored to produce functional proteins by a secondary indel near the primary indel site. This phenomenon is known as "compensatory frameshift" [32], and may explain the low amino acid identity in LIS I and II. These LIS regions could be the result of successive indel followed by compensatory frameshift events.…”
Section: Discussionmentioning
confidence: 99%